2022
DOI: 10.1259/bjr.20220137
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of unilateral magnetic resonance-guided focused ultrasound in comparison with unilateral deep brain stimulation for the treatment of medically refractory essential tremor in England

Abstract: Objectives: This study aims to ascertain the cost effectiveness of Magnetic Resonance Guided focused Ultrasound (MRgFUS) for the treatment of medically refractory Essential Tremor (mrET) in England. Essential Tremor (ET) is the most common movement disorder affecting approximately 1 million in the United Kingdom causing considerable societal impact affecting patients, carers and the wider health-service. Medical treatment has mixed efficacy with approximately 25–55% of ET medication refractory. Deep Brain Stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These alterations can be sensitively captured in diagnostic ultrasound such as time-harmonic ultrasound elastography, so whether there is an impact on high-intensity focused ultrasound is currently unclear. (3) The hypertension may also impact on the long-term brain remodeling after minor brain lesion therapy such as thalamectomy. Our series of works have demonstrated topological changes in regional structural and functional connectivity networks due to Vim lesion and potential dopaminergic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alterations can be sensitively captured in diagnostic ultrasound such as time-harmonic ultrasound elastography, so whether there is an impact on high-intensity focused ultrasound is currently unclear. (3) The hypertension may also impact on the long-term brain remodeling after minor brain lesion therapy such as thalamectomy. Our series of works have demonstrated topological changes in regional structural and functional connectivity networks due to Vim lesion and potential dopaminergic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thalamotomy by MRgFUS touts numerous advantages, including minimal invasiveness, preservation of surrounding tissue, and precise millimeter-level targeting [2]. Numerous studies have substantiated that MRgFUS thalamotomy not only delivered tremor relieve exceeding 78% for medically refractory essential tremor (ET) and over 85% improvement for tremor-dominant Parkinson’s disease (PD) [2], but also saved about 68.28% expenses and 0.03 additional quality-adjusted life-years (QALYs) per patient [3]. These breakthroughs have resulted in the wide approval of MRgFUS devices for addressing movement disorders by multiple regulatory agencies.…”
Section: Introductionmentioning
confidence: 99%
“…Given the substantial financial costs associated with many of these treatments, this is an important potential barrier to access and uptake that should be considered in future work. [79][80][81] All rights reserved. No reuse allowed without permission.…”
Section: Limitationsmentioning
confidence: 99%
“…In 2020, NHS England agreed to fund MRgFUS treatment of ET for NHS patients effective from April 2021. A recent health economic study (14) also demonstrated the favourable cost-effectiveness profile of MRgFUS for the treatment of ET in England. With MRgFUS funding in place for ET, it is important to understand patients' perspectives and experiences of this new type of treatment.…”
Section: Introductionmentioning
confidence: 98%